Measuring ACPA in the general population or primary care: is it useful? - Axel Finckh; Celine Lamacchia; Delphine Courvoisier; O. Studer; E. Trunk; B. Gilbert (RMD Open)
Rheumatoid arthritis (RA) is associated with a significant disease burden and high costs for society. Because the disease has identifiable preclinical stages, screening and prevention have become a possibility in RA. Anticitrullinated peptide antibodies (ACPAs) are arguably the most likely candidate biomarker to screen for RA. This paper reviews the evidence for the use of ACPAs as a screening test in the broader general population, to identify individuals at high risk of subsequent onset of RA. We will review the diagnostic properties of the test and its positive and negative predictive value in different settings. We will discuss how ACPA testing could effectively be integrated in a broader screening strategy for RA.